1987
DOI: 10.1111/j.1442-9071.1987.tb00066.x
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Ocular Disorders in 1000 Queensland Primary Schoolchildren

Abstract: This study was designed to establish the prevalence of ocular disorders in a paediatric population. There have been numerous studies conducted in this area with similar objectives. However, the majority of these adopted principally visual screening protocols, whilst others comprised incomplete examinations. A feature of this study is the inclusion of both cycloplegic refraction and ophthalmoscopy under mydriasis. Almost without exception other studies omit these procedures.One early and comprehensive ophthalmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 7 publications
2
20
1
Order By: Relevance
“…Consistent with other studies, we found that orthophoria was the main phoric state at distance fixation2 3 5 8 and the distribution of heterophoria size was leptokurtic 3 9 19 20. In our population, the distribution was skewed towards exophoria in both the 6- and 12-year-old children.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with other studies, we found that orthophoria was the main phoric state at distance fixation2 3 5 8 and the distribution of heterophoria size was leptokurtic 3 9 19 20. In our population, the distribution was skewed towards exophoria in both the 6- and 12-year-old children.…”
Section: Discussionsupporting
confidence: 91%
“…While many studies of similarly aged children have reported that orthophoria is the most frequent state for near fixation,2 5 8 we found that exophoria predominated. After stratification, this finding persisted in the European Caucasian and East Asian populations.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…A number of studies were carried out in the early 1970s and the 1980s on relatively large groups of unselected primary school children from the socio-economic extremes (generally aged 5 to 12 years), and indicated a prevalence of myopia ranging from approximately 3% to 13% (see Table 1) [25-29]. Two of those early studies investigated children largely from underprivileged, rural, families [26,27], and the other was of children from several, middle to upper socio-economic class private schools [25].…”
Section: Introductionmentioning
confidence: 99%
“…6 Although the number of children with accommodative esotropia is not well known, strabismus has been estimated to affect between 0.5% and 4% of children. [7][8][9][10] Esodeviations comprise >50% of this, 11 with refractive accommodative esotropia clearly playing a significant role. Evidence exists suggesting that hyperopia may be under strong genetic control.…”
mentioning
confidence: 99%